2006
DOI: 10.1016/s1441-3582(06)70054-4
|View full text |Cite
|
Sign up to set email alerts
|

Service Satisfiers and Dissatisfiers among Malaysian Consumers

Abstract: Much research has focused on identifying the dimensions of service quality based on the assumption that each dimension contributes equally to customer satisfaction and dissatisfaction. Limited study has been done to investigate whether separate factors may act as satisfiers and dissatisfiers. This paper examines the issue using a sample of critical incidents collected from Malaysian consumers across a broad range of service industries. It was found that the determinants of satisfaction and dissatisfaction need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Moreover, the approach used in this study only provides information about whether or not an attribute plays a role in predicting customer satisfaction. However, attributes are dissimilar in terms of their effects on customer satisfaction (Johnston, 1995;Kueh, 2007). Tantakasem and Lee (2007) argued that service quality attributes that are related to customer satisfaction can be classified as:…”
Section: Discussion and Mangrial Implicationsmentioning
confidence: 99%
“…Moreover, the approach used in this study only provides information about whether or not an attribute plays a role in predicting customer satisfaction. However, attributes are dissimilar in terms of their effects on customer satisfaction (Johnston, 1995;Kueh, 2007). Tantakasem and Lee (2007) argued that service quality attributes that are related to customer satisfaction can be classified as:…”
Section: Discussion and Mangrial Implicationsmentioning
confidence: 99%
“…Moreover, previous research has found that the drivers of customer satisfaction may vary from those of customer dissatisfaction; they are not necessarily two extremes of a continuum but rather a distinct set of factors that drive satisfaction and dissatisfaction (Cadotte & Turgeon, ; Johnston, ; Kueh, ; Alegre & Garau, ). Thus, some sets of factors may generate satisfaction, yet their absence does not necessarily generate dissatisfaction (Albayrak & Caber, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Neutrals are similar to aforementioned indifferent quality elements in that they seemingly have no impact on satisfaction regardless of performance level. Similarly, Kueh (2006), also using the CIT identified the identical four types of relationships across a range of service types. The author classified an attribute as critical if it was identified as both a top satisfier and top dissatisfiers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%